Needs Analysis for Developing an Islamic-Integrated Fluid Module - Khoiro Mahbubah; Agus Santoso; Durrotul Afiyah (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2025)
Module are one of the learning resources that an important role in supporting the success of the learning process and support in delivering material systematically, directed, and in accordance with the established learning outcomes. This study aims to obtain information about the need for integrated science and Islamic Fluid module. This type of research is descriptive qualitative with research subjects of 23 students in Science Education département who have programmed the Fluid course. The data of this study includes an analysis of the need for integrated science and Islamic Fluid module. This research instrument is a questionnaire filled out by students and an interview sheet. The results of the study obtained by the integrated science and Islamic Fluid module scored 83% (category very needed) and the available module are still limited, so the development of integrated science and Islamic Fluid module is very needed.